Knowledge and health facility–related determinants of men’s support for spousal cervical cancer screening: a mixed-methods study in a rural county of Southeastern Kenya - Taabu Wambua, Ruth (International Journal Of Community Medicine And Public Health, 2026)
Background: Globally, cervical cancer is the fourth leading cause of cancer deaths. In Kenya, it is ranked as the second cause of cancer-related deaths among females. Men’s knowledge of cervical cancer is essential in reducing cervical cancer burden. This study was conducted in Makueni County, Kenya, to establish knowledge and health facility-related determinants of men’s support for spousal cervical cancer screening in Kenya. Methods: Quantitative and qualitative data were collected using structured questionnaires from married men aged 18–64 years attending three rural Health facilities in Makueni County, Kenya. Participants were recruited via simple random sampling from purposively selected hospitals. Quantitative data were analysed using descriptive and inferential methods, while qualitative data employed thematic coding. Key informant interviews with nurses heading Maternal and Child Health services provided qualitative insights. Ethical approval was obtained and participants consented. Results: Male support for spousal cervical cancer screening was low, with 82% showing minimal involvement. Knowledge factors such as knowledge of cervical cancer signs or symptoms, causative agent, risk factors, prevention, screening frequency, and screening duration was strongly associated with male involvement (p<0.001). Awareness that men can transmit the causative agent to women also showed a significant relationship with involvement (p=0.019). The level of male support was significantly associated with service availability, presence of signage, and cost (p<0.005). Conclusions: Male support for their spouses cervical cancer screening was low, calling for increased health education and awareness among men to boost support for cervical cancer screening initiatives. Health facilities should ensure continuous access to free services and promote their awareness.